Carbohydrate supplementation does not improve 10 km swimming intermittent training - Baldassarre, R.; Sacchetti, M.; Patrizio, F.; Nicolò, A.; Scotto di Palumbo, A.; Bonifazi, M.; Piacentini, M. F (Sports, 2018)
The aim of the present study was to test the effectiveness of carbohydrate (CHO) feeding supplemented every 2.5-km, as in official races, on the performance, rating of perceived exertion (RPE), and glycaemia during a 10-km intermittent training workout in elite open-water swimmers. A randomized crossover design was used. Participants completed two 10-km intermittent training sessions (20 × 500-m). The relative velocity was expressed in percentage of a single 500-m. Glycaemia was monitored by continuous glucose monitoring. Participants had to ingest either 1 L of tap water (WAT; 0.50 L·h-1) or 120 g of CHO in the form of 8% solution (60 g·h-1). The 15-point RPE scale was used during the trials. A two-way ANOVA for repeated measures was performed (p < 0.05). The relative velocity of each 500-m was not significantly different between the two trials. No significant differences emerged in the relative velocity of the last 500-m between trials. Average RPE was not statistically different between the two trials (11 ± 3 in WAT and 12 ± 3 in CHO). In the last 500-m, glycaemia was significantly higher in the CHO trial (5.92 ± 0.47 mmol·L-1 in CHO; 5.61 ± 0.61 mmol·L-1 in WAT). CHO ingestion did not improve performance or affect RPE during a 10-km intermittent training in elite open-water swimmers